WATER REALITY IN UKRAINE AND WORLDWIDE - Dolina, L. F.; Mashykhina, P. B.; Karpo, A. A.; Mishchenko, A. A. (Science and Transport Progress, 2017)
Purpose. The paper analyzes the state of water management in Ukraine and worldwide, as well as the best practices in this area. Methodology. The study was carried out based on the analysis of literature sources and reporting data on the state of water management in Ukraine, European countries, the USA (2010-2016). Findings. The water state analysis in the regions of Ukraine showed that the quality in most cases is close to or meets the requirements for drinking water. Drinking tap water requires post-treatment in all regions of the country. The main issue for today is the production of the necessary equipment for treatment plants. Unfortunately, not all equipment is produced in Ukraine. The condition of rural water pipelines is of particular concern. Among the tested pipelines 7.3% do not comply with the rules and regulations. At the same time, only 25% of villages in Ukraine are provided with centralized water supply. Originality. The authors presented the results of a comprehensive review of the world's issues on disinfection of drinking and waste water, where various methods are used, partly in combination with each other in Ukraine and the worldwide. The main unresolved issue today is the issue of the residual quantity of drugs in the drinking water. The main environmental threat of the world scale is the presence of medicines in drinking water. The treatment facilities are not suitable for the decomposition or trapping of medicinal products. Nowhere in the world there is protection from these substances. One of the key issues in the solution of drinking water production is seawater desalination. To reduce the cost of desalination of sea water the SWRO-membrane technology is used. Practical value. Water problems are number one problems all over the world and in Ukraine as well. It is necessary to provide for additional financing to solve problems in the preparation and purification of waters, not with whatever funds remain, taking into account the fact that water is the basis of life on earth as a whole, the health and life of the nation depends on the quality of the water supply source.